Upaya Kepolisian Dalam Penegakan Hukum Terhadap Tindak Pidana Perdagangan Wanita Dan Anak Di Kota Samarinda Provinsi Kalimantan Timur - EMILDA KUSPRANINGRUM , HARIS RETNO SUSMIYATI (Fakultas Hukum Universitas Mulawarman, 2008)
According to Asean Development Bank (ADB) report that for about one to two millionpeople had been sold. Most of them are from poor country, 150.000 from West Asia country and225.000 from North West Asia Country. The main problem in reducing trafficking in women andchild is the weaknesses of law enforcement. Solvement of this case is an ice mount fenomenawhere the tripe case which accord is more than success to solve and brought to the law process byassosieted party.Key words : penegakan hukum (law enforcement), tindak pidana (criminal), perdagangan wanitadan anak (trafficking in women and children), kepolisian (police department).